The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31219/osf.io/54duz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data Mining Bisnis

Abstract: Bisnis tidak berjalan pada ruang tertutup. Oleh karena itu keberhasilan dalam menjalankan bisnis tidak bergantung pada bagaimana cara menjalankan bisnis, akan tetapi pada bagaimana menjalankannya jika dibandingkan dengan lainnya. Kunci untuk membuat perbedaan terletak pada pemakaian data yang tersimpan pada sistem yang digunakan untuk bisnis sehari hari.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…As a function of the robot joint velocities and accelerations, Paes et al [9] proposed time and energy-optimal paths in a limited workspace. Paryanto and his research group [10] studied the energy profile and dynamic characteristics for a 6DOF robot with different speeds and payloads in an assembly system. The energy-optimal robot motion parameters inside the manufacturing work-cell of mechanical structure and control logics of industrial robots were modeled by Gadaleta et al [11,12].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As a function of the robot joint velocities and accelerations, Paes et al [9] proposed time and energy-optimal paths in a limited workspace. Paryanto and his research group [10] studied the energy profile and dynamic characteristics for a 6DOF robot with different speeds and payloads in an assembly system. The energy-optimal robot motion parameters inside the manufacturing work-cell of mechanical structure and control logics of industrial robots were modeled by Gadaleta et al [11,12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their study is limited to specific motion profiles that are not affected by manufacturing cycle times. Software-simulated power data were used in several studies to identify robot dynamics and predict energy-efficient robotic motion [8,16]. Pellicciari et al [17] suggested a numerical technique for lowering industrial robots' energy usage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The influence of ice slurry on the pump power is not a simple linear problem [15]. The optimal design of an ice slurry system should analyze and support a design process characterized by low energy consumption [16] through the optimal selection of power, e.g., pumps [17][18][19], drive unit [20][21][22], or control algorithm [23][24][25], depending on the conditions of use. Currently, most studies on ice slurry systems are based on experiments, and the microscopic characteristics of ice particles passing through different channels (vertical Slit channel [26], Rectangular Channel [27], etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The ever-growing awareness of the negative consequences on the environment of the energy needs of manufacturing systems has led to the study and development of methodologies to reduce energy consumption. Industrial robots make up a significant part on the total electrical energy consumed in the manufacturing sector [1]. Studies to reduce the energy consumption of these systems have been recently reviewed by Carabin et al [2].…”
Section: Introductionmentioning
confidence: 99%